Incorporating Wireless Frequency-Modulated Technology into Your Practice - Atcherson, Samuel R. (Seminars in Hearing, 2014)
Frequency-modulated (FM) technology has high potential to increase patient communicative quality of life and independence in complex listening situations. However, FM technology is often difficult to integrate into and/or justify for audiology practice, and teenage and adult patients may fail to realize the potential of FM technology to augment their hearing. This is especially true for hearing aid or implant device users who must add additional equipment and may feel that their current ear-level technology is the end solution for their listening needs. This article presents possible solutions for increasing FM technology adoption using a practice-management and patient-focused approach.
Keywords: Adoption; FM; quality of life; practice management; speech understanding in noise